Micro-Credit and the Socioeconomic Wellbeing of Women. A Case Study of Queen of Peace Co-Operative Credit Union - Abayateye, T.O. (University Of Ghana, 2017)
Women lack economic resources, and have limited access to financial and non-financial resources. Over the years, credit facilities have been made available to women in the hope of improving their wellbeing. However, some school of thought have remained critical about the role micro-credit plays in the wellbeing of women. Given this, this study sought to explore the extent to which micro-credit can improve or contribute to the wellbeing of women, with emphasis on their income levels, asset accumulation and how they dealt with health issues. The study was conducted in the context of La Nkwantanang Madina Assembly. A qualitative approach was used to gain the experiences of women members of Queen of Peace Co-operative Credit Union. Findings from the study show that majority of the women experienced increases in their income levels, bringing about increased contribution to household expenditures and in the education of their wards. Support from spouses of the women also played a role in this regard. The findings from the study also showed that a significant number of the women experienced increases in asset accumulation as well as the credit enabling them to deal with health issues. The study also found out that the purpose for which the loan was put, played a significant role in the socioeconomic wellbeing of the women. Organizations seeking to improve the wellbeing of women through the provision of micro-credit can focus on helping the women invest in income generating activities, as this might trickle down to other areas of their wellbeing such as their health and the education of their wards.
Thesis (MPhil.)
Keywords: Micro-Credit; Socioeconomic Wellbeing; Co-Operative Credit Union; Credit Facilities; Women; Ghana